2019
DOI: 10.15406/mojap.2019.06.00276
|View full text |Cite
|
Sign up to set email alerts
|

A detailed study of the course, branching pattern and dimensions of the uterine and vaginal arteries and their branches

Abstract: Introduction: Despite the critical role of the uterine artery (UA) and vaginal artery (VA) in the blood supply to the pelvic organs and cavity, there is a paucity of descriptions of their origin, course, and dimensions. Aim:The aim of the study was to present a detailed account based on a cadaveric study on pelvic halves of 31 female embalmed cadavers belonging an Indian population.Methods: A total of 31 female cadavers (62 pelvic halves) in the age group of 34-75 years belonging an Indian population were diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, several studies mainly in the last 10 years have demonstrated a significant spectrum of anatomical variations with regards to the origin of the uterine artery which differs from our traditional knowledge. In 2019, Lakshmi et al published a study of a total of 31 Indian female cadavers that showed that the uterine artery originated from the anterior division of the internal iliac artery in all the cadavers without any variations whatsoever [11]. In 2020, Orhan et al…”
Section: Significancementioning
confidence: 99%
“…However, several studies mainly in the last 10 years have demonstrated a significant spectrum of anatomical variations with regards to the origin of the uterine artery which differs from our traditional knowledge. In 2019, Lakshmi et al published a study of a total of 31 Indian female cadavers that showed that the uterine artery originated from the anterior division of the internal iliac artery in all the cadavers without any variations whatsoever [11]. In 2020, Orhan et al…”
Section: Significancementioning
confidence: 99%